Numerical Simulation of an Intramedullary Elastic Nail: Expansion Phase and Load-Bearing Behavior - Pascoletti, Giulia; Cianetti, Filippo; Putame, Giovanni; Terzini, Mara; Zanetti, Elisabetta M. (Frontiers in Bioengineering and Biotechnology, 2018)
The Marchetti-Vicenzi’s nail is an intramedullary device where six curved nails are kept straight by a closing ring in order to allow their insertion into the medullary canal of a long bone; in a following step, these nails stabilize the fracture due to the ring withdrawal and to the consequent elastic expansion of the nails. Pre-clinical testing of this sort of device is strongly advocated in order to be able to foresee their stability inside the medullary canal and to quantify their stiffening action on a broken bone. In this numerical work an MB (Multi Body) model of the device has been developed, with the dual purpose of evaluating forces between the bone and the system components during its progressive opening and verifying the behaviour of the stabilized bone when it undergoes external loading. Different solutions, for flexible body modelling (discretization with lumped parameters, ‘flexible body’, ‘FE Part’) have been analysed and compared in terms of accuracy of results and required computational resources. Contact parameters have been identified and criteria to simplify geometries and therefore to reduce simulation times have been given. Results have allowed identifying some critical issues in the design of these nails and in their use, and giving suggestions for new designs. On the whole, a tool for the optimization and for the pre-clinical testing of elastic intramedullary nails has been given.